The Importance of Oral Health in Immigrant and Refugee Children - Crespo, Eileen (Children (Basel), 2019)
According to the Migration Policy Institute, 2017 data revealed that a historic high 44.5 million people living in the United States (US) were foreign-born (Zong, J., et.al., 2019), more than double the number from 1990 (U.S. Immigrant Population and Share over Time. 1850-Present, 2019). Since the creation of the Refugee Resettlement Program in 1980, refugee families have settled in the US more than in any other country in the world (Radford, J., 2019). In 2018, for the first time, Canada overtook the US in numbers of refugees accepted (Zong, J., et. al., 2019). Foreign-born people now account for 13.7% of the total US population (Zong, J., et. al., 2019). Further, a quarter of children in the United States currently live in households with at least one foreign-born parent (America’s Children in Brief: Key National Indicators of Well-Being, 2018). These population shifts are important to note because immigrant and refugee families bring cultural influences and health experiences from their home countries which can greatly affect the overall health and well-being of children. For these new arrivals, oral health is often a significant health issue. The severity of dental disease varies with country of origin as well as cultural beliefs that can hinder access to care even once it is available to them (Obeng, C.S. Culture and dental health among African immigrant school-aged children in the United States, 200; Tiwari, T.; Albino, J. Acculturation and Pediatric Minority Oral Health Interventions, 2017). As pediatricians and primary care providers, we should acknowledge that oral health is important and impacts overall health. Healthcare providers should be able to recognize oral health problems, make appropriate referrals, and effectively communicate with families to address knowledge gaps in high-risk communities.